Sustainable technology empowerment in functional beverage production - Mariana, Rina Rifqie; Gunawan, Aditia Gustiana; Kusuma, Fuad Indra (University of Islam Malang, 2025)
This community service program was aimed at improving the local functional beverage businesses and was focused on the application of a vacuum evaporator as a relevant technology to improve the sustainability and competitiveness of local functional beverage industries. This was a continuation of the program where a sugarcane juice extractor was developed to produce syrup as the base material. Specifically, the goals of the current initiative were 1) improvement of the efficiency of production and quality of the end products, 2) the development of syrup based functional beverages that could be enriched with local nutritious materials, and 3) the empowerment of local entrepreneurs, farmer groups, and women’s groups on value-added processing. The project was implemented through participatory training, demonstration of the technology, and hands-on workshops to 40 community members which included, lecturers, students, community leaders and MSME actors. After the vacuum evaporator was installed, there was a 60% reduction in the heating time, a 75% increase in production capacity and syrup viscosity and stability were improved without loss of flavor. As part of preparing tangible outputs, training materials, SOPs, and documentation of prototypes were also prepared. The program achieved enhanced product marketplace and raised MSME income and awareness on sustainable processing. In community-based entrepreneurship, the application of vacuum evaporation community technology demonstrated positive outcomes and innovation of functional beverages.